Моделирование микропроцессорной тепловой защиты асинхронного электродвигателя - Сивокобыленко, В. Ф.; Ткаченко, С. Н. (Видавництво Національного університету «Львівська політехніка», 2007)
This article describes mathematical simulation of digital relay protection and automatics of induction motor with squirrel-caged rotor. It also introduces stator and rotor windings overheat protection algorithm. The measuring method is based on real-time active rotor resistance calculation with afterwards comparison of calculated value to the known rotor resistance value in cold condition.